A panorama of mathematics : pure and applied : Conference Mathematics and Its Applications, November 14-17, 2014, Kuwait University, Safat, Kuwait - Fonseca, Carlos M. da; Huynh, D. V.; Kirkland, Steve; Vu, Kim Tuan; Conference on Mathematics and its Applications (Contemporary mathematics, 2016)
This volume contains the proceedings of the Conference on Mathematics and its Applications-2014, held from November 14-17, 2014, at Kuwait University, Safat, Kuwait. Papers contained in this volume cover various topics in pure and applied mathematics ranging from an introductory study of quotients and homomorphisms of C-systems, also known as contextual pre-categories, to the most important consequences of the so-called Fokas method. Also covered are multidisciplinary topics such as new structural and spectral matricial results, acousto-electromagnetic tomography method, a recent hybrid imaging technique, some numerical aspects of sonic-boom minimization, PDE eigenvalue problems, von Neumann entropy in graph theory, the relative entropy method for hyperbolic systems, conductances on grids, inverse problems in magnetohydrodynamics, location and size estimation of small rigid bodies using elastic far-fields, and the space-time fractional Schrodinger equation, just to cite a few.